Studi Perencanaan Manajemen Sumber Daya Manusia Tenaga Pendidik di SD Islam Palembang - Mulyadi Eko Purnomo; Prasetyo Budi Utomo; Mgs Nazarudin (Studia Manageria, 2021)
This study aims to explain: how the planning, recruitment, selection andplacement, training and development, evaluation, compensation, supervision and constraints in the development of human resources for educators at SD Islam Fatimah Palembang. The research methodology used is a qualitative descriptive approach. Data collection techniques with observation, interviews and documentation. The analysis used data reduction, display and data verification. The results of the study are: planning for selection of prospective educators, recruitment planning systems, planning for training and human resource development as an effort to improve the quality of improving the quality of education, evaluations carried out using three stages, namely monthly evaluation, mid-semester and year-end evaluation. the provision of compensation and provision of allowances can increase the motivation for the performance of educators. The supervision system is carried out by setting standards, supervision, overcoming obstacles that are still faced in the planning process of Human Resources for Educators regularly.